Safety and efficacy of Lactobacillus rhamnosus CNCM I‐3698 and Lactobacillus farciminis CNCM I‐3699 as a feed additive for all animal species. (30th April 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Lactobacillus rhamnosus CNCM I‐3698 and Lactobacillus farciminis CNCM I‐3699 when used as a silage additive in forage for all animal species. The additive is the result from the fermentation of milk‐based broth with L. rhamnosus CNCM I‐3698 and L. farciminis CNCM I‐3699. It is intended to be used in easy and moderately difficult to ensile materials at a minimum proposed application rate of 2.5 × 10 7 and maximum 8 × 10 7 VFU/kg complete feed for all animal species. The data provided do not allow a full characterisation of the additive, and therefore, uncertainty remains on the nature of the product in terms of viability, on the ratio between the active agents and on the shelf‐life of the additive. Both strains fulfil the requirements of the Qualified Presumption of Safety (QPS) approach to the assessment of safety and consequently, are presumed safe for the target animals, consumers of products from animals receiving the additive and the environment. The additive should be considered a respiratory sensitiser. In the absence of data, no conclusions can be drawn on the irritancy of the additive to skin and eyes or on its dermal sensitisation potential. No conclusions can be drawn on the efficacy of the additive to improve the ensiling process of easy and moderately difficult to ensile materials.